PENGARUH DANA KAMPUNG TERHADAP PENINGKATAN PEMBANGUNAN JALAN (STUDI PADA KAMPUNG LIMANBENAWI KECAMATAN TRIMURJO KABUPATEN LAMPUNG TENGAH) - Nyono Hadi; Sudarman Mersa (P3M STISIPOL Dharma Wacana Metro, 2018)
This article discusses the influence of village funds on improving road construction. Taking a study at Kampung Liman Benawi in Trimurjo District, Central Lampung Regency. The research approach is quantitative. Using the help of questionnaire instruments, the total sample involved in this study amounted to 30 respondents. The results of the product moment correlation analysis above obtained the value of X2 = 0.547, then consulted with the value of X2table at the real level of 5% = 0.312, so that X2 count> X2 table at the real level of 5%. Thus it can be concluded that there is a relationship between the Village funds and the construction of a lap road in Liman Benawi Village, Trimurjo District, Central Lampung. While the magnitude of the influence between and villages for the construction of road lapen is 29.92% (coefficient of determination).